Optimization and economic analysis of grid-photovoltaic electric boat charging station in Kuala Terengganu - Roslan, U.; Salleh, N.A.; Muda, W.M.W. (2016)
This study evaluates the feasibility of developing grid-photovoltaic electric boat charging station in Kuala Terengganu using simulation-based method. The main focus is on reducing the dependency on subsidy spent by the government in fisheries sector and encouraging green technology in commercial sector. All data such as solar radiation, amount of subsidy received by fishermen, and fishing activities were collected for the selected area. Economic analyses of the proposed system are discussed based on payback period and net present cost (NPC). The comparison between the proposed system and the grid-only system is done based on the production and consumption of electricity per year, the NPC and emission of pollutant. The system also generates high income from selling energy to the grid with tariff rates RM 1.49/kWh. It is concluded that the proposed system is feasible to be developed in the selected area with the payback period and the NPC are 8.2 years and RM 759,098, respectively. The results also show that the performance of the proposed system is better than grid-only system in all the interested parameters.